Juridical Construction of Legislative Term Limits in Indonesia - Andika Wijaya; Karlinae D. Bangas; Hilyatul Asfia; Normala (Journal of Constitutional and Governance Studies, 2025)
Legislative term limits are an important aspect of the legal context of legislative power. This research attempts to examine the legal construction of legislative term limits in an effort to understand their legal basis and impact on the political and governance system. In the exercise of the legislative function, term limits become a crucial tool to prevent excessive consolidation of power and to ensure the rotation of political elites. This research involves the analysis of various laws and regulations governing legislative term limits at different levels of government. The legal construction analysis covers aspects such as the constitutional basis, the legislative process involved in setting term limits, and the legal considerations underlying the decision. In addition, this research will examine the implications of term limits for political stability, accountability and representation in a democratic system. The findings of this research are expected to provide a deeper understanding of the concept of legislative term limits, both in the context of legal theory and implementation practice. The impact of legislative term limits on political dynamics and governance can provide valuable insights for policy makers, academics and the general public concerned with the legal aspects of the system. Keywords: Construction, Periodicity, Legislative. Abstrak Pembatasan masa jabatan legislatif merupakan suatu aspek penting dalam konteks hukum yang berkaitan dengan kekuasaan legislatif. Penelitian ini mencoba untuk menyelidiki konstruksi yuridis pembatasan masa jabatan legislatif sebagai upaya untuk memahami landasan hukum dan dampaknya terhadap sistem politik dan pemerintahan. Dalam menjalankan fungsi legislasi, pembatasan masa jabatan menjadi instrumen yang menentukan untuk mencegah konsolidasi kekuasaan yang berlebihan dan memastikan rotasi elit politik. Penelitian ini melibatkan analisis terhadap berbagai peraturan perundang-undangan yang mengatur pembatasan masa jabatan legislatif di berbagai tingkatan pemerintahan. Analisis konstruksi yuridis mencakup aspek-aspek seperti dasar konstitusional, proses legislasi yang terlibat dalam penetapan pembatasan masa jabatan, dan pertimbangan hukum yang mendasari keputusan tersebut. Selain itu, penelitian ini juga mengeksplorasi implikasi pembatasan masa jabatan terhadap stabilitas politik, akuntabilitas, dan representasi dalam sistem demokratis. Hasil penelitian ini diharapkan dapat memberikan pemahaman yang lebih mendalam tentang konsep pembatasan masa jabatan anggota legislatif, baik dalam konteks teori hukum maupun praktik implementasinya. Implikasi dari pembatasan masa jabatan anggota legislatif terhadap dinamika politik dan tatanan pemerintahan dapat memberikan wawasan berharga bagi pembuat kebijakan, akademisi, dan masyarakat umum yang peduli terhadap aspek-aspek hukum dalam sistem politik ketatanegaraan suatu negara. Kata kunci: Construction, Periodicity, Legislative.